Driving model of land use change on the evolution of carbon stock: a case study of Chongqing, China - Luoshan Zheng; Yangbing Li; Yan Chen; Rong Wang; Shijie Yan; Chunhua Xia; Bing Zhang; Jing’an Shao (Environmental Science and Pollution Research, 2023)

Advances, challenges, and prospects in microalgal-bacterial symbiosis system treating heavy metal wastewater - Xing-Rui Zhou; Rong Wang; Cong-Cong Tang; Cristiano Varrone; Zhang-Wei He; Zhi-Hua Li; Xiaochang C. Wang (Chemosphere, 2023)

Long-term crowding stress induces chronic inflammatory response and declines the immunity of grass carp (Ctenopharyngodon idella) - Wenhan Li; Dapeng Li; Qiushi Yang; Lu Liu; Jieya Liu; Jiamin Lu; Yin Wang; Rong Tang; Li Li; Xi Zhang (Aquaculture, 2023)

Native ApxIIA secreted by Actinobacillus pleuropneumoniae induces apoptosis in porcine alveolar macrophages dependent on concentration and acylation - Hao Tang; Rong Wang; Siqi Pang; Weiyao Han; Qiuhong Zhang; Qiong Fang; Xiabing Chen; Qi Huang; Dexin Qiu; Rui Zhou; Lu Li (Veterinary Microbiology, 2023)

Non-steroidal anti-inflammatory drugs (NSAIDs) in the environment: Recent updates on the occurrence, fate, hazards and removal technologies - Jia-yuan Lin; Yuan Zhang; Yu Bian; Yi-xin Zhang; Rong-zhu Du; Ming Li; Yue Tan; Xue-song Feng (Science of The Total Environment, 2023)

Dynamic human exposure to airborne bacteria-associated antibiotic resistomes revealed by longitudinal personal monitoring data - Rong-min Zhang; Xin-lei Lian; Li-wei Shi; Liuyiqi Jiang; Shan-shan Chen; Wen-qing Haung; Jia-en Wu; Fei-jing Wu; Jian Sun; Xiao-ping Liao; Yun-xiao Chong; Ya-hong Liu; et al. (Science of The Total Environment, 2023)

Seasonal dynamics of dissolved organic matter bioavailability coupling with water mass circulation in the South Yellow Sea - Shengkang Liang; Mingzheng Zhang; Xinke Wang; Hongguan Li; Shanshan Li; Haoyang Ma; Xiulin Wang; Zengrui Rong (Science of The Total Environment, 2023)

Relative contribution of roots and symbiotic fungi to wheat nitrogen uptake and N2O emissions under straw burial - Zheng-Rong Kan; Yanling Li; Ruoyan Yang; Xinyu Yang; Qihang Wei; Ahmad Latif Virk; Jianying Qi; Feng-Min Li; Zichang Zhang; Haishui Yang (Rhizosphere, 2023)

LC-MS-based untargeted metabolomics reveals the mechanism underlying prostate damage in a type 2 diabetes mouse model - Rong Qi; Shao-san Kang; Yongchao Pei; Mingming Liu; Yufan Zhou; Bo Guan; Xinduo Zhang; Zhiguo Li; Fenghong Cao (Reproductive Biology, 2023)

Carbon-neutral potential in treatment of N, N-dimethylformamide-containing industrial wastewater: Comparative investigation of energy conservation, carbon reduction and expenditure between UASB and Fenton process - Xinwei Tan; Yuqin Fan; Xinzheng Zhang; Tianwei Hao; Rong Chen; Tao Zhang; Rui Lu; Jianliang Sun; Dapeng Li; Yang Pan; Yu-You Li; Zhe Kong (Journal of Water Process Engineering, 2023)

Preparation and characterization of polyvinyl alcohol/glutaraldehyde cross-linked chitosan/ε-Polylysine degradable composite film and its antibacterial effect - Shuangfeng Guo; Xiuyun Zhang; Rong Ma; Xiangzhen Ge; Huishan Shen; Wei Liang; Guoquan Zhang; Wenhao Li (Journal of Food Engineering, 2023)

Three decades of shade trees improve soil organic carbon pools but not methane uptake in coffee systems - Hao Sun; Fulan Zhang; Syed Turab Raza; Yingmo Zhu; Tao Ye; Li Rong; Zhe Chen (Journal of Environmental Management, 2023)

Effects of iron additives on the removal of antibiotics and antibiotic resistance genes in anaerobic fermentation of food waste - Xiaotian Li; Langping Zhu; Rong Ma; Xiaozhi Zhang; Changquan Lin; Youqian Tang; Zhuoshen Huang; Chunming Wang (Journal of Environmental Management, 2023)

Metabolic cross-feeding enhances branched-chain aldehydes production in a synthetic community of fermented sausages - Kaihao Liu; Peng Yang; Xudong Zhang; Di Zhang; Liu Wu; Lan Zhang; Huan Zhang; Guoliang Li; Ruren Li; Liangyan Rong (International Journal of Food Microbiology, 2023)

Prevalence and characterization of Staphylococcus aureus and Staphylococcus argenteus isolated from rice and flour products in Guangdong, China - Dongli Rong; Zhenjie Liu; Jiahui Huang; Feng Zhang; Qingping Wu; Jingsha Dai; Yuanyu Li; Miao Zhao; Qi Li; Jumei Zhang; Shi Wu (International Journal of Food Microbiology, 2023)

Widely targeted metabolic profiling provides insights into variations in bioactive compounds and antioxidant activity of sesame, soybean, peanut, and perilla - Habtamu Kefale; Senouwa Segla Koffi Dossou; Feng Li; Nanjun Jiang; Rong Zhou; Lei Wang; Yanxin Zhang; Donghua Li; Jun You; Linhai Wang (Food Research International, 2023)

Effect of geographical origins and pile-fermentation on the multi-element profiles of ripen Pu-erh tea revealed by comprehensive elemental fingerprinting - Jiayi Zhu; Le Chen; Yue Chen; Yuting Rong; Yongwen Jiang; Fuqiao Liu; Qinghua Zhou; Xuehong Wei; Haibo Yuan; Junjie Zhang; Jia Li (Food Control, 2023)

A strategy to prepare low-temperature curable photosensitive polyimide with good comprehensive performance - Shan Huang; Xialei Lv; Xingwang Lai; Jinhui Li; Yao Zhang; Siyao Qiu; Guoping Zhang; Rong Sun (Chemical Engineering Journal, 2023)

Chemical constituents of the leaves of Coriaria nepalensis and their chemotaxonomic significance - Min Tan; Xiao-Lan Chen; Xuan-Qin Chen; Rong-Tao Li; Zhi-Jun Zhang (Biochemical Systematics and Ecology, 2023)

A Field Model Test Method of Tunnel-Type Anchorages in Rock Mass and Its Application in Railway Suspension Bridge Engineering - Aiqing Wu; Yihu Zhang; Rong Luo; Dongdong Xu; Lei Fan; Huoming Zhou; Xiangchao Wu; Yongjin Wu; Yujie Li (Rock Mechanics and Rock Engineering, 2023)

Shoot Production of Solanum tuberosum L. ‘Yansi’ Using a Simple Continuous Immersion Airlift Bioreactor Culture System - Hang-Lin Song; Rong-de Jin; Xue-Li Quan; Ji-De Zhang; Wen-Wen Qi; Xi-Hua Cui (Potato Research, 2023)

Orthodontic craniofacial pattern diagnosis: cephalometric geometry and machine learning - Yuqing Zhou; Bochun Mao; Jiwu Zhang; Yanheng Zhou; Jing Li; Qiguo Rong (Medical & Biological Engineering & Computing, 2023)

Morphological and Pull-Out Mechanical Properties of Alfalfa Roots in the Seedling Stage - Chaobo Zhang; Rong Li; Jing Jiang; Qihong Yang (Journal of Soil Science and Plant Nutrition, 2023)

Classification of Glomerular Pathology Images in Children Using Convolutional Neural Networks with Improved SE-ResNet Module - Xiang-Yong Kong; Xin-Shen Zhao; Xiao-Han Sun; Ping Wang; Ying Wu; Rui-Yang Peng; Qi-Yuan Zhang; Yu-Ze Wang; Rong Li; Yi-Heng Yang; Ying-Rui Lv (Interdisciplinary Sciences: Computational Life Sciences, 2023)

The expression of CD86 in CD3+CD56+ NKT cells is associated with the occurrence and prognosis of sepsis-associated encephalopathy in sepsis patients: a prospective observational cohort study - Sheng-long Chen; Xiao-yu Liu; Jun-hong Huang; Lu-hua Xian; Xu-sheng Li; Kang-rong Wang; Jing Li; Tian-cao Zhang; Guo-ge Huang; Xin-qiang Liu; Hong-ke Zeng; Mao-hua Zhou; et al. (Immunologic Research, 2023)

Projected Regional 1.50°C and 2.00°C Warming Threshold-crossing Time Worldwide Using the CMIP6 Models - Yali Meng; Keqin Duan; Wei Shang; Peihong Shi; Shuangshuang Li; Ying Cheng; Rong Chen; Zhaopeng Zhang (Chinese Geographical Science, 2023)

Comparison of demineralized bone matrix with different cycling crushing times in posterolateral fusion model of athymic rats - Shao-Lin Ji; Xiao-Dan Zhao; Li-Min Wang; Cheng-Gang Pang; Wen-Jing Li; Kun-Xiu Song; Rong-Xing Ma; Rui-Feng Li; Jing-Yu Zhang; Yong-Cheng Hu (Cell and Tissue Banking, 2023)

Triptolide induces PANoptosis in macrophages and causes organ injury in mice - Hong-Rui Zhang; Ya-Ping Li; Zi-Jian Shi; Qi-Qi Liang; Si-Yuan Chen; Yi-Ping You; Tao Yuan; Rong Xu; Li-Hui Xu; Dong-Yun Ouyang; Qing-Bing Zha; Xian-Hui He (Apoptosis, 2023)

Synergistic leaching process for ion-exchange ammonium from weathered crust elution deposited rare earth tailings with potassium magnesium compound eluent - Xiaoju Li; Junxia Yu; Xiaodi Li; Guoping Song; Ze Ouyang; Rong Wang; Zhenyue Zhang; Chunqiao Xiao; Ruan Chi (Environmental Science and Pollution Research, 2023)

First principles insights into the interaction mechanism of iron doped thermally activated kaolinite with Cd and Pb pollutants in organic solid waste incineration flue gas - Yang-wen Wu; Rong Guo; Li-juan Sun; Xin-yue Zhou; Jia-le Zhou; Hai-yuan Zhao; Yi-fei Yu; Zhuang Hu; Bin Hu; Ji Liu; Bing Zhang; Li Zhao; et al. (Waste Management, 2023)

Experimental infection and co-infection with Chinese strains of Ehrlichia canis and Babesia vogeli in intact and splenectomized dogs: Insights on clinical, hematologic and treatment responses - Jilei Zhang; Jiawei Wang; Patrick John Kelly; Yuanyuan Zhang; Min Li; Jing Li; Rong Zhang; Yaoyao Wang; Ke Huang; Jinfeng You; Haixiang Qiu; Xiaofeng Zheng; et al. (Veterinary Parasitology, 2023)

Mapping high-resolution energy consumption CO2 emissions in China by integrating nighttime lights and point source locations - Mengdi Wang; Rong Li; Meigen Zhang; Liangfu Chen; Fan Zhang; Congwu Huang (Science of The Total Environment, 2023)

Mesocosm experimental study on sustainable riparian restoration using sediment-modified planting eco-concrete - Yi Li; Shengxiang Rong; Chi Zhang; Hongqiang Chu; Pengcheng Wei; Shiqiang Tao (Science of The Total Environment, 2023)

Enantioselective effect of the chiral fungicide tebuconazole on the microbiota community and antibiotic resistance genes in the soil and earthworm gut - Chao-Feng Li; Yi-Rong Zhang; Zhen-Chao Tan; Hui-Juan Xu; Cheng-Lan Liu (Science of The Total Environment, 2023)

Over-expression of UDP-glycosyltransferase UGT353G2 confers resistance to neonicotinoids in whitefly (Bemisia tabaci) - Tian-hua Du; Cheng Yin; Lian-you Gui; Jin-jin Liang; Shao-nan Liu; Bu-li Fu; Chao He; Jing Yang; Xue-gao Wei; Pei-pan Gong; Ming-jiao Huang; Hu Xue; et al. (Pesticide Biochemistry and Physiology, 2023)

Effects of zero-valent iron and magnetite on ethanol and lactic acid production in the anaerobic fermentation of food waste - Xiaotian Li; Rong Ma; Langping Zhu; Xiaozhi Zhang; Changquan Lin; Youqian Tang; Zhuoshen Huang; Chunming Wang (Journal of Environmental Management, 2023)

A new ground-motion model to predict horizontal PGA, PGV, and spectral acceleration for small-to-moderate earthquakes in the capital circle region of China - Bin Zhang; Xiaojun Li; Yanxiang Yu; Jize Sun; Mianshui Rong; Su Chen (Journal of Asian Earth Sciences, 2023)

Curcumin-mediated photodynamic treatment extends the shelf life of salmon (Salmo salar) sashimi during chilled storage: Comparisons of preservation effects with five natural preservatives - Hui-Ming Chen; Quan Zhou; Li-Jun Huang; Jun Lin; Jia-Fei Liu; Zi-Yong Huang; Rong-Lin Zhang; Jing-Jing Wang; Yong Zhao; Yong-Ning Wu; Xing-Fen Yang; Wei-Liang Wu (Food Research International, 2023)

Fabrication of natural W1/O/W2 double emulsions stabilized with gliadin colloid particles and soybean lecithin - Xuan Zhang; Xing Rong; Duo Zhang; Yongkang Yang; Bin Li (Food Hydrocolloids, 2023)

Revealing mechanisms of triclosan on the removal and distribution of nitrogen and phosphorus in microalgal-bacterial symbiosis system - Sheng-Long Chen; Tian-Yang Wang; Cong-Cong Tang; Rong Wang; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Environmental Pollution, 2023)

Biochar facilitates methanogens evolution by enhancing extracellular electron transfer to boost anaerobic digestion of swine manure under ammonia stress - Gaojun Wang; Peng Fu; Bo Zhang; Ji Zhang; Qiuyi Huang; Gaofei Yao; Qian Li; Mawuli Dzakpasu; Jianfeng Zhang; Yu-You Li; Rong Chen (Bioresource Technology, 2023)

Nanoparticle (NP)-mediated APOC1 silencing to inhibit MAPK/ERK and NF-κB pathway and suppress breast cancer growth and metastasis - Shaomin Liu; Fengqian Zhang; Yixia Liang; Guo Wu; Rong Liu; Xiuling Li; Phei Er Saw; Zhonghan Yang (Science China Life Sciences, 2023)

Quantification of multiple environmental controls on lipid biomarkers in common marine diatoms and dinoflagellates - Zhong Cao; Rong Bi; Chuanli Zhang; Jiaxuan Cui; Li Li; Yang Ding; Meixun Zhao (Marine Biology, 2023)

Mesoscopic measurement of damage and shear bands of granite residual soil using Micro-CT and digital volume correlation - Cheng-sheng Li; Bing-xin Zhang; Zhi-jun Liu; Ling-wei Kong; Rong-jun Shu (Journal of Mountain Science, 2023)

Hydrogeochemical characterization and precursor anomalies of hot springs in the North Tianshan orogen - Zhihua Ding; Xiaocheng Zhou; Chengguo Wang; Jingchao Li; Miao He; Jiao Tian; Kayimu Saimaiernaji; Chengying Zhu; Wei Yan; Rong Ma; Xinyong Li; Na Li; et al. (Applied Geochemistry, 2023)

Low-protein diet promotes nitrogen retention efficiency via enhanced renal urea reabsorption and microbial hydrogen incorporation in the rumen of goats - Xiu Min Zhang; Wen Xun Chen; Qiong Xian Yan; Chao Wang; Bo Lin; Si Yu Yi; Rong Wang; Zhi Yuan Ma; Qiu Shuang Li; Arjan Jonker; Xue Zhao Sun; Suntorn Wittayakun; et al. (Animal Feed Science and Technology, 2023)

Multifunctional dumbbell probes-based logic circuits: microRNAs logic detection and tumor cells identification - Xin Liu; Baiying Li; Qian Liu; Li Zhang; Rong Zhao; Di Wu; Luojia Wang; Zhongzhong Wang; Guoming Xie; Wenli Feng (Analytica Chimica Acta, 2023)

High phytoplankton diversity in eutrophic states impedes lake recovery - Rong Wang; C. Patrick Doncaster; Wenxiu Zheng; Min Xu; Hui Yang; Yun Li; Yongjiu Cai; Yanjie Zhao; Enlou Zhang; Xiangdong Yang; Boqiang Qin (Journal of Biogeography, 2023)
Aim The widely observed positive response of productivity to biodiversity, known as the biodiversity‐productivity relationship (BPR), underpins nature‐based solutions for mitigating and adapting to global changes. Little is known of the role of such emergent processes in the restoration of damaged ecosystems. Here, we test for evidence of a BPR in degraded freshwater lakes, and its role in underpinning or undermining lake recovery from eutrophic states. Location Lower Yangtze and Huaihe river basins, China, East Asia. Taxa Freshwater phytoplankton; also macrophytes, fish, zooplankton and zoobenthos. Methods A systematic review of biodiversity studies was conducted to enumerate freshwater biodiversity change during eutrophication, encompassing 572 samples from 155 lakes in East China. Empirical samples were then taken of 93 phytoplankton communities from 38 lakes in ecologically degraded states of eutrophication. Samples were analysed for niche overlap in relation to biodiversity and productivity, and metrics of network structure indicative of community stability. Results Reviewed publications on eutrophication in East China lakes revealed losses in biodiversity of macrophytes, fishes, zooplankton and zoobenthos but not phytoplankton. Empirically sampled eutrophic lakes maintained high phytoplankton biodiversity through niche differentiation, and phytoplankton biodiversity correlated positively with biomass, in line with the expectations of BPR. Conclusions The positive effect of biodiversity on phytoplankton productivity in eutrophic lakes acts in opposition to the negative impacts on productivity induced by eutrophication‐management strategies of nutrient suppression. In degraded systems, the BPR contributes to sustaining productivity of lake phytoplankton communities, impeding recovery from a eutrophic state. This is a case of the BPR playing an undesirable role at the ecosystem level. Lake recovery programmes need to anticipate that the control of phytoplankton biomass will depend on reducing nutrients to a level sufficient to degrade the internal structure of the phytoplankton community.

N, N-bis (2-hydroxyethyl) malonamide based amidoxime functionalized polymer immobilized in biomembranes for highly selective adsorption of uranium(VI) - Yang Li; Ze-Yang Wang; Qi Ren; Feng Zhang; Xu-Xin Li; Qiang Wu; Rong Hua; Ze-Yi Yan; Yun Wang (Chemosphere, 2023)

Residual chlorine persistently changes antibiotic resistance gene composition and increases the risk of antibiotic resistance in sewer systems - Jingyi Zhang; Zuxin Xu; Wenhai Chu; Feng Ju; Wei Jin; Peng Li; Rong Xiao (Water Research, 2023)

Vertical distribution and transport of microplastics in the urban atmosphere: New insights from field observations - Zhen Yuan; Cheng-Lei Pei; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Kai Zhang; Ming-Gang Cai; Xiang-Rong Xu (Science of The Total Environment, 2023)

An integrative analysis of lipidomics and transcriptomics in various mouse brain regions in response to real-ambient PM2.5 exposure - Shuangjian Qin; Huixian Zeng; Qizhen Wu; Qingqing Li; Mohammed Zeeshan; Lizhu Ye; Yue Jiang; Rui Zhang; Xinhang Jiang; Miao Li; Rong Zhang; Wen Chen; et al. (Science of The Total Environment, 2023)

The impact of crop residue return on the food–carbon–water–energy nexus in a rice–wheat rotation system under climate warming - Li-Yao Zhou; Yong-he Zhu; Zheng-Rong Kan; Feng-Min Li; Feng Zhang (Science of The Total Environment, 2023)

Inactivation of airborne pathogenic microorganisms by plasma-activated nebulized mist - Li Guo; Pengyu Zhao; Yikang Jia; Zifeng Wang; Min Chen; Hao Zhang; Dingxin Liu; Yong Zhang; Xiaohua Wang; Mingzhe Rong (Journal of Hazardous Materials, 2023)

Selective adsorption and special recognition of roxarsone (ROX) from water by utilizing novel core-shell magnetic molecularly imprinted polymers - Zhipan Wen; Runqiao Chen; Ge Zhang; Shen Li; Yalei Zhang; Xiaoping Liao; Gang Cheng; Rong Chen (Journal of Cleaner Production, 2023)

Interfacial permeation preparation of ZIF-8 in reactive deep eutectic for efficient adsorption and selective removal of Congo red - Yiwen Li; Huanhuan Zhang; Shikuan Xu; Yangyang Wang; Qi Guo; Rong Li; Yanjun Xing (Journal of Environmental Chemical Engineering, 2023)

Research advancement on magnetic nanomaterial demulsifier for oil-water separation - Rong Wang; Junyi Li; Haigang Zhou; Siyuan Liu; Wei Sun; Chenyang Zhang (Journal of Environmental Chemical Engineering, 2023)

Experimental study on visualization of TBAB hydrate formation in confined small channels - Qi-Rong Zuo; Ming Gao; Peng Kong; Li-Xin Zhang (Fuel, 2023)

Widely targeted metabolomics and HPLC analysis elaborated the quality formation of Yunnan pickled tea during the whole process at an industrial scale - Yan Hou; Honglin Mao; Fengmei Lu; Cunqiang Ma; Shaoxian Zhu; Guoyou Li; Siqi Huang; Yi Zhang; Caiyou Lv; Rong Xiao (Food Chemistry, 2023)

The role of total antioxidant capacity and malondialdehyde of seminal plasma in the association between air pollution and sperm quality - Lipeng Li; Tengfei Feng; Ruiting Wu; Yaling Zhang; Ning Wang; Mengqi Wu; Yaxian Pang; Sujuan Yang; Aimin Yang; Dengsuo Zhang; Guimin Hao; Rong Zhang (Environmental Pollution, 2023)

A spheropolyhedral-based discrete element lattice Boltzmann method for simulation of non-spherical adhesive particulate flow - Ye-Cheng Qian; Rong-Rong Cai; Li-Zhi Zhang (Computer Physics Communications, 2023)

Alignment of Fe3O4/CNT electrodes via magnetic blade printing for wireless stress-direction-recognizing strain sensor - Guangwei Wang; Chenhao Cong; Xianbing Zheng; Hongjiang Li; Fuhao Jiang; Xuhao Wang; Rong Li; Mingliang Jin; Pengfei Zhang; Junru Li; Chuanwei Zhang; SeHyun Kim; et al. (Chemical Engineering Journal, 2023)

Icariin inhibits hypertrophy by regulation of GPER1 and CaMKII/HDAC4/MEF2C signaling crosstalk in ovariectomized mice - Wenxia Zhao; Xiaoli Shan; Xueqin Li; Shuang Lu; Lei Xia; Huihua Chen; Chen Zhang; Wei Guo; Ming Xu; Rong Lu; Pei Zhao (Chemico-Biological Interactions, 2023)

In situ Strontium isotope stratigraphy of fish teeth in deep-sea sediments from the western Clarion-Clipperton Fracture Zone, eastern Pacific Ocean - Tianyi Wang; Yanhui Dong; Fengyou Chu; Wen Zhang; Xiaohu Li; Rong Su; Liyan Tian (Chemical Geology, 2023)

Insights into roles of triclosan in microalgal–bacterial symbiosis system treating wastewater - Cong-Cong Tang; Tian-Yang Wang; Rong Wang; Cristiano Varrone; Zixuan Gan; Zhang-Wei He; Zhi-Hua Li; Xiaochang C. Wang (Bioresource Technology, 2023)

Contrasting effects of rice husk and its biochar on N2O emissions and nitrogen leaching from Lei bamboo soils under subtropical conditions - Rong Zhou; Zhe Chen; Ali EI-Naggar; Linlin Tian; Chengpeng Huang; Zhen Zhang; Kumuduni Niroshika Palansooriya; Yongfu Li; Bing Yu; Scott X. Chang; Yanjiang Cai (Biology and Fertility of Soils, 2023)

Impact of nitrogen addition on single and mixed tree leaf litter decomposition depends on N forms in subtropical China - Pan-Pan Wu; Zao Zhang; Rui Li; Jing-Hao Ji; Rong Mao (Applied Soil Ecology, 2023)

Hypervirulent Klebsiella pneumoniae detection methods: a minireview - Qi-bin Zhang; Peng Zhu; Shun Zhang; Yan-jing Rong; Zuo-an Huang; Li-wan Sun; Ting Cai (Archives of Microbiology, 2023)

Differences in particulate matter retention and leaf microstructures of 10 plants in different urban environments in Lanzhou City - Rong Huang; Qing Tian; Yue Zhang; Zhini Chen; Yonghua Wu; Zizhen Li; Zebin Wen (Environmental Science and Pollution Research, 2023)

Moderately delayed maturation of composting promotes the reduction of guild-plant pathogenic fungi within vegetable waste - Zijian Lv; Chengyuan Tao; Jiawei Zhang; Zongzhuan Shen; Dongsheng Wang; Bei Wang; Hongjun Liu; Rong Li (Environmental Science and Pollution Research, 2023)

Identification of novel serum protein biomarkers in the context of 3P medicine for intravenous leiomyomatosis: a data-independent acquisition mass spectrometry-based proteomics study - Zhitong Ge; Penghui Feng; Zijuan Zhang; Zhiyong Liang; Rong Chen; Jianchu Li (EPMA Journal, 2023)

Concentrations and homologue patterns of SCCPs and MCCPs in the serum of the general population of adults in Hangzhou, China - Jianyun Zhang; Hanyu Liao; Yanhong Chen; Xue Li; Rong Chen; Shufen Han; Shuren Liu; Shanshan Yin (Chemosphere, 2023)

Short-term feeding of dietary florfenicol influences gut microbiome and growth performance of fast-growing Silurus meridionalis - Zhimin Zhang; Qiushi Yang; Weitong Xu; Rong Tang; Li Li; Dapeng Li (Aquaculture, 2023)

Serum levels of IL-6/IL-10/GLDH may be early recognition markers of anti-tuberculosis drugs (ATB) -induced liver injury - Huai-Rong Xiang; Yun Li; Xuan Cheng; Bei He; Hua-Min Li; Qi-Zhi Zhang; Bin Wang; Wen-Xing Peng (Toxicology and Applied Pharmacology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Understanding key genetic make-up of different coat colour in Bayinbuluke sheep through a comparative transcriptome profiling analysis - Lihua Zhang; Long Liang; Xuemei Zhang; Wen Rong Li; Haiying Li; Sangang He (Small Ruminant Research, 2023)

Characterization of elastoplastic behavior and retrieval of active zone depth for expansive soil slopes in the middle-route channel head of the South-to-North Water Diversion Project, China, using InSAR time series - Ziyuan Li; Jun Hu; Xing Zhang; Wanji Zheng; Wenqing Wu; Yaogang Chen; Pinjun Tang; Rong Gui (Remote Sensing of Environment, 2023)

Projection of drought-flood abrupt alternation in a humid subtropical region under changing climate - Rong Wang; Xianghu Li; Qi Zhang; Junxiang Cheng; Jianfeng Li; Dan Zhang; Yuanbo Liu (Journal of Hydrology, 2023)

Clinical poisoning events involving yunaconitine may be highly correlated with metabolism-based interactions: A critical role of CYP3A4 - Xiaocui Li; Yu Fu; Huawei Qiu; Xueyu Xu; Tingting Lin; Weiqing Hou; Weiying Chen; Rong Zhang; Zhongqiu Liu; Lijun Zhu (Food and Chemical Toxicology, 2023)

Zn anode surface engineering for stable zinc-ion batteries: Carbon dots incorporated mesoporous TiO2 as a coating layer - Tian-Bing Song; Qian-Li Ma; Xi-Rong Zhang; Jia-Wen Ni; Tian-Le He; Huan-Ming Xiong (Chemical Engineering Journal, 2023)

An anaerobic dynamic membrane bioreactor (AnDMBR) system enhanced the biogas conversion efficiency and stability of mesophilic codigestion with waste activated sludge and food waste - Bao-Shan Xing; Yi Zhang; Rui-Qi Zhang; Jing Ma; Xiang-Lin Chang; Xi-Fang Tang; Yu-You Li; Xiaochang C. Wang; Rong Chen (Chemical Engineering Journal, 2023)

Thermochromic smart window utilizing passive radiative cooling for Self-Adaptive thermoregulation - Rong Zhang; Renzhi Li; Peng Xu; Wenhuan Zhong; Yifan Zhang; Zhenyang Luo; Bo Xiang (Chemical Engineering Journal, 2023)

Electrospun polyvinyl alcohol-chitosan dressing stimulates infected diabetic wound healing with combined reactive oxygen species scavenging and antibacterial abilities - Haibing Liu; Rong Chen; Pinkai Wang; Jinlang Fu; Zinan Tang; Jiajun Xie; Yanhong Ning; Jian Gao; Qiang Zhong; Xin Pan; Ding Wang; Mingyuan Lei; et al. (Carbohydrate Polymers, 2023)

Treatment of fresh leachate by anaerobic membrane bioreactor: On-site investigation, long-term performance and response of microbial community - Weifu Yan; Yulin Wang; Yemei Li; Chao Rong; Dou Wang; Chunxiao Wang; Yubo Wang; Yee-lok Yuen; Fanny Fong Wong; Ho-Kwong Chui; Yu-You Li; Tong Zhang (Bioresource Technology, 2023)

Transcriptome and Metabolome Integrated Analysis Reveals the Mechanism of Cinnamomum bodinieri Root Response to Alkali Stress - Haozhang Han; Lihua Zhang; Suhua Li; Rong Zhao; Fang Wang; Rong Dong; Xiaoli Wang (Plant Molecular Biology Reporter, 2023)

Spautin-1 Protects Against Mild TBI-Induced Anxiety-Like Behavior in Mice via Immunologically Silent Apoptosis - Hui-Tao Miao; Rong-Xin Song; Yue Xin; Lu-Ying Wang; Jin-Meng Lv; Na-Na Liu; Zhi-You Wu; Wei Zhang; Yan Li; Dong-Xue Zhang; Li-Min Zhang (NeuroMolecular Medicine, 2023)

Effects of Different Plant Species on the Chemical and Microbial Properties of Coastal Saline-Alkaline Soils in Southeast China - Xinxin Zhang; Xindi Zhao; Qi Chai; Rong Liu; Zhenhua Li; Minting Liu (Journal of Soil Science and Plant Nutrition, 2023)

BMI Modifies the Association Between Depression Symptoms and Serum Copper Levels - Wu Hongrong; Li Qingqi; Gao Rong; Tang Shuangyang; Zhang Kaifang; Zhao Jianfeng (Biological Trace Element Research, 2023)

Corrigendum to “Divergent responses of moss- and lichen-dominated biocrusts to warming and increased drought in arid desert regions. Agricultural and Forest Meteorology, 303 (2021) 108387 - Xinrong Li; Rong Hui; Peng Zhang; Naiping Song (Agricultural and Forest Meteorology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Dietary selenium requirement for on-growing grass carp, Ctenopharyngodon idellus - Feifei Chen; Ziyi Zhang; Li Wang; Haodong Yu; Xuezhen Zhang; Keming Rong (Aquaculture, 2023)

Method for quantitative extraction of copper hydroxide nanoparticles from farmland soil - Xin-Yuan Li; Yuan Yang; Peng Huang; Ying-Rong Wang; Yu-Lin Nie; Li Zhang; Qiang Wang (Science of The Total Environment, 2023)

Detection of spatiotemporal changes in ecological quality in the Chinese mainland: Trends and attributes - Yang Li; Haifeng Tian; Jingfei Zhang; Siqi Lu; Zhixiang Xie; Wei Shen; Zhicheng Zheng; Mengdi Li; Peijun Rong; Yaochen Qin (Science of The Total Environment, 2023)

One new elemane sesquiterpenoid glycoside and five glycoglycerolipids from Pittosporum truncatum with anti-bacterial activity - Rong Huang; Ji-Li Deng; Sheng-Nan Guan; Jia-Qi Ding; Xiu-Yun Zhang (Phytochemistry Letters, 2023)

Novel_miR-1517 mediates CYP6CM1 to regulate imidacloprid resistance in Bemisia tabaci (Hemiptera: Gennadius) - Pei-Pan Gong; Xue-Gao Wei; Shao-Nan Liu; Jing Yang; Bu-Li Fu; Jin-Jin Liang; Ming-Jiao Huang; Tian-Hua Du; Cheng Yin; Yao Ji; Chao He; Jin-Yu Hu; et al. (Pesticide Biochemistry and Physiology, 2023)

Cytochrome P450 CYP6DB3 was involved in thiamethoxam and imidacloprid resistance in Bemisia tabaci Q (Hemiptera: Aleyrodidae) - Xuegao Wei; Jinyu Hu; Jing Yang; Cheng Yin; Tianhua Du; Mingjiao Huang; Buli Fu; Peipan Gong; Jinjin Liang; Shaonan Liu; Hu Xue; Chao He; et al. (Pesticide Biochemistry and Physiology, 2023)

Ejiao peptide-iron chelates regulate the metabolism of iron deficiency anemia mice and improve the bioavailability of iron - Xiang-Rong Cheng; Yu-Yao Chen; Cong-Cong Cao; Jia-Hui Ma; Chen-Xi Zhang; Zi-Wei Zhao; Qian Wu; Yuan-Yuan Li; Mitchell N. Muskat; Guo-Qing Wu (Food Bioscience, 2023)

Effects of dietary supplementation of Anabaena sp. PCC7120 expressing VP28 protein on survival and histopathology after WSSV infection in Macrobrachium nipponense - Yupei Tong; Jia Yang; Li Wang; Xiaoping Chi; Chan Zhu; Rong Yin; Le Zhang; Yaru Li; Chunyan Zhao; Rui Jia (Fish & Shellfish Immunology, 2023)

Interaction of metabolism-related pathway gene variants with bisphenol A exposure on serum lipid profiles - Heng He; Fuwei Zhang; Shuang Zhou; Shanshan Zhang; Lu Wang; Jiaoyuan Li; Qiang Zeng; Ying Zhu; Jianbo Tian; Jiang Chang; Liming Cheng; Qing Lu; et al. (Environmental Toxicology and Pharmacology, 2023)

Strong and continuous MXene/sodium alginate composite fibers prepared by immersion rotary jet spinning process with outstanding electromagnetic interference shielding performance - Guoxin Zhao; Chao Sui; Linlin Miao; Junjiao Li; Lei Wen; Gong Cheng; Chenxi Zhao; Weizhe Hao; Yuna Sang; Jiaxuan Li; Zhuochao Zhang; Yushun Zhao; et al. (Chemical Engineering Journal, 2023)

Involvement of Abnormal p-α-syn Accumulation and TLR2-Mediated Inflammation of Schwann Cells in Enteric Autonomic Nerve Dysfunction of Parkinson’s Disease: an Animal Model Study - Wenwen Jiang; Yue Cheng; Ye Wang; Jing Wu; Zhe Rong; Li Sun; Yan Zhou; Kezhong Zhang (Molecular Neurobiology, 2023)

CORM-3 alleviates the intestinal injury in a rodent model of hemorrhage shock and resuscitation: roles of GFAP-positive glia - Li-Min Zhang; Yue Xin; Rong-Xin Song; Wei-Chao Zheng; Jin-Shu Hu; Jie-Xia Wang; Zhi-You Wu; Dong-Xue Zhang (Journal of Molecular Histology, 2023)

Characteristics of mesenchymal stem cells and their exosomes derived from giant panda (Ailuropoda melanoleuca) endometrium - Yu-Liang Liu; Jia-Song Chen; Jun-Hui An; Zhi-Gang Cai; Jing-Chao Lan; Yuan Li; Xiang-Wei Kong; Ming-Yue Zhang; Rong Hou; Dong-Hui Wang (In Vitro Cellular & Developmental Biology - Animal, 2023)

Thymic tuft cells: potential “regulators” of non-mucosal tissue development and immune response - Jun Sun; Ming-xin Li; Yi-meng Xie; Ya-ru Zhang; Yu-rong Chai (Immunologic Research, 2023)

Shape Classification of Cloud Particles Recorded by the 2D-S Imaging Probe Using a Convolutional Neural Network - Rong Zhang; Haixia Xiao; Yang Gao; Haizhou Su; Dongnan Li; Lei Wei; Junxia Li; Hongyu Li (Journal of Meteorological Research, 2023)

Catalytic probes based on aggregation-induced emission-active Au nanoclusters for visualizing MicroRNA in living cells and in vivo - Wenhao Shu; Xuetao Zhang; Hongmei Tang; Linna Wang; Manxiao Cheng; Jingwen Xu; Rong Li; Xiang Ran (Analytica Chimica Acta, 2023)

High-resolution forest age mapping based on forest height maps derived from GEDI and ICESat-2 space-borne lidar data - Xudong Lin; Rong Shang; Jing M. Chen; Guoshuai Zhao; Xiaoping Zhang; Yiping Huang; Guirui Yu; Nianpeng He; Li Xu; Wenzhe Jiao (Agricultural and Forest Meteorology, 2023)

Diverse early diagenetic processes of ferromanganese nodules from the eastern Pacific Ocean: evidence from mineralogy and in-situ geochemistry - Rong Su; Fengyue Sun; Xiaohu Li; Fengyou Chu; Guosheng Sun; Jie Li; Hao Wang; Zhenggang Li; Cong Zhang; Weiyan Zhang; Xiaohan Gong; Yanhui Dong (International Geology Review, 2023)

Effects of discharge angle of jet from a slot orifice on cooling performance for a perforated air ducting system in dairy cattle barn - Mengbing Cao; Ruimin Yang; Christopher Y. Choi; Li Rong; Guoqiang Zhang; Kaiying Wang; Xiaoshuai Wang (Computers and Electronics in Agriculture, 2023)

An electronic sense-based machine learning model to predict formulas and processes for vegetable-fruit beverages - Hai-Bin Ren; Bao-Long Feng; Hong-Yue Wang; Jing-Jian Zhang; Xiao-Sen Bai; Fei Gao; Yan Yang; Qi Zhang; Ye-Hui Wang; Li-Li Wang; Ya-Ting Rong; Yu-Lin Sun; et al. (Computers and Electronics in Agriculture, 2023)

Long-term in-situ starvation and reactivation of co-digestion with food waste and corn straw in a continuous AnDMBR: Performance, sludge characteristics, and microorganism community - Bao-Shan Xing; Xiang-Lin Chang; Sifan Cao; Dong Wu; Yi Zhang; Xi-Fang Tang; Yu-You Li; Xiaochang C. Wang; Rong Chen (Science of The Total Environment, 2023)

Achieving high yield and nitrogen agronomic efficiency by coupling wheat varieties with soil fertility - Keyu Ren; Minggang Xu; Rong Li; Lei Zheng; Huiying Wang; Shaogui Liu; Wenju Zhang; Yinghua Duan; Changai Lu (Science of The Total Environment, 2023)

Novel fatty acids-governed cannibalism in beneficial rhizosphere Bacillus enhances biofilm formation via a two-component system OmpS/R and toxin transporter - Rong Huang; Qing Li; Dandan Wang; Haichao Feng; Nan Zhang; Jiahui Shao; Qirong Shen; Zhihui Xu; Ruifu Zhang (Science Bulletin, 2023)

Hydroclimate changes since the last glacial maximum from sedimentary biomarkers in a crater lake in the Great Khingan Mountains, Northeast China - Weiwei Sun; Enlou Zhang; Enfeng Liu; Yang You; Jingjing Li; Zhenyu Ni; Xianqiang Meng; Wenfang Zhang; Rong Chen (Quaternary Science Reviews, 2023)

Ergostane-type sterols and sesquiterpenes with anti-neuroinflammatory activity from a Nigrograna species associated with Clematis shensiensis - Liang-Liang Zhai; Ting-Ting Jiang; Rong Zhang; Jian-Nan Li; Yi-Jie Zhai; Qiang Zhang; Ding Li; Wen-Bo Han (Phytochemistry, 2023)

Towards advanced mariculture wastewater treatment by bacterial-algal symbiosis system with different bacteria and algae inoculation ratios - Hongwei Rong; Yingying Li; Jingyin Wang; Qi Zhang; Baihui Cui; Dabin Guo (Journal of Water Process Engineering, 2023)

Mechanisms and adsorption capacities of ball milled biomass fly ash/biochar composites for the adsorption of methylene blue dye from aqueous solution - Huaiyan Li; Jie Kong; Haiting Zhang; Jiale Gao; Yan Fang; Jiaqi Shi; Tao Ge; Ting Fang; Yanhong Shi; Rong Zhang; Ningyuan Zhang; Xinju Dong; et al. (Journal of Water Process Engineering, 2023)

Identification and characterization of goat milk key flavor compounds and their precursors in electron beam irradiation and pasteurization on raw - Chunlu Wen; Ya Chen; Madina; Linlu Zhang; Yue Peng; Bai Rong; Linjie Xi; Shengqi Jiang; Jiangtao Yu; Junqing Bai; Niu Wei; Li Kui; et al. (Innovative Food Science & Emerging Technologies, 2023)

Effect of flue gas components on the removal of cadmium pollutants by transition metal-modified activated carbon: Density functional theory and thermodynamic study - Xin-Yue Zhou; Jia-Le Zhou; Rong Guo; Yin-jie Liu; Yi-fei Yu; Bing Zhang; Yang-Wen Wu; Li Zhao; Qiang Lu (Fuel, 2023)

Corrigendum to “Co-folding of soy protein isolates and shellac by structural interplays to induce hydrogels” [Food Hydrocolloids 139 (2023) 108527] - Yang Guo; Zhi-guo Zhang; Jing Cai; Wei-rong Li; Ling-yun Chen; Wei-cheng Wu (Food Hydrocolloids, 2023)

Amorphous biomineral-reinforced hydrogels with dramatically enhanced toughness for strain sensing - Jia-hua Liu; Zhengyi Mao; Yuhan Chen; Yunchen Long; Haikun Wu; Junda Shen; Rong Zhang; Oscar W.H. Yeung; Binbin Zhou; Chunyi Zhi; Jian Lu; Yang Yang Li (Chemical Engineering Journal, 2023)

Ultra-stable, sensitive and broadband photodetector based on large-area 2D bismuth oxyselenide film for multiband image sensing - Shuai Ren; Shiyong Gao; Ping Rong; Lin Li; Mingyi Zhang; Huiqing Lu; Jun Yan; Duoduo Ling; Shujie Jiao; Jinzhong Wang (Chemical Engineering Journal, 2023)

Investigating the thermal conductivity and flame-retardant properties of BN/MoS2/PCNF composite film containing low BN and MoS2 nanosheets loading - Lei Yang; Wei Xu; Xiaolong Shi; Menglin Wu; Ziyi Yan; Qing Zheng; Gongneng Feng; Li Zhang; Rong Shao (Carbohydrate Polymers, 2023)

Determination of partial denitrification kinetic model parameters based on batch tests and metagenomic sequencing - Xinwei Su; Xiao-rong Zhu; Jianwei Li; Lei Wu; Xiyao Li; Qiong Zhang; Yongzhen Peng (Bioresource Technology, 2023)

Spatiotemporal characteristics of extreme hydrometeorological events and its potential influencing factors in the Huaihe River Basin, China - Rong Gan; Dandan Li; Changzheng Chen; Feng Yang; Xinyu Zhang; Xiaomin Guo (Stochastic Environmental Research and Risk Assessment, 2023)

HucMSC-EVs Facilitate In Vitro Development of Maternally Aged Preantral Follicles and Oocytes - Ying-Yi Zhang; Weijie Yang; Yi Zhang; Zhanhong Hu; Yingyan Chen; Yerong Ma; Anran Yang; Zhan Shi; Hanjing Zhou; Peipei Ren; Libing Shi; Jiamin Jin; et al. (Stem Cell Reviews and Reports, 2023)
Follicle developmental capacity and oocyte quality decline with advanced maternal age. Extracellular vesicles from human umbilical cord mesenchymal stem cells (HucMSC-EVs) act as a potential therapeutic product in the treatment of age-related ovarian dysfunction. In vitro culture (IVC) of preantral follicles is a useful method for understanding the mechanism of follicle development and is a promising means for improving female fertility. However, whether HucMSC-EVs have beneficial effects on aged follicle development during IVC has not yet been reported. Our research demonstrated that follicular development with single-addition withdrawal of HucMSC-EVs was better than that with continuous treatment with HucMSC-EVs. HucMSC-EVs facilitated the survival and growth of follicles, promoted the proliferation of granulosa cells (GCs), and improved the steroid hormone secretion of GCs during IVC of aged follicles. Both GCs and oocytes could uptake HucMSC-EVs. Moreover, we observed elevated cellular transcription in GCs and oocytes after treatment with HucMSC-EVs. The RNA sequencing (RNA-seq) results further validated that the differentially expressed genes are related to the promotion of GC proliferation, cell communication, and oocyte spindle organization. Additionally, the aged oocytes displayed a higher maturation rate, presented less aberrant spindle morphology, and expressed a higher level of the antioxidant protein Sirtuin 1 (SIRT1) after treatment with HucMSC-EVs. Our findings suggested that HucMSC-EVs can improve the growth and quality of aged follicles and oocytes in vitro through the regulation of gene transcription, which provides evidence for HucMSC-EVs as potential therapeutic reagents to restore female fertility with advanced age. Graphical Abstract

Synergistic effect of elevated glucose levels with SARS-CoV-2 spike protein induced NOX-dependent ROS production in endothelial cells - Jiahao Zhang; Li He; Rong Huang; Juan Felipe Alvarez; David H. Yang; Qihao Sun; Fengqin Wang; Zhiyong Peng; Nanhui Jiang; Lianjiu Su (Molecular Biology Reports, 2023)

HSPA12A was identified as a key driver in colorectal cancer GWAS loci 10q26.12 and modulated by an enhancer–promoter interaction - Zequn Lu; Linyun Fan; Fuwei Zhang; Chaoqun Huang; Yimin Cai; Can Chen; Gaoyuan Li; Ming Zhang; Jinyu Huang; Caibo Ning; Yanmin Li; Wenzhuo Wang; et al. (Archives of Toxicology, 2023)

Characteristics of PM2.5 and Its Reactive Oxygen Species in Heating Energy Transition and Estimation of Its Impact on the Environment and Health in China—A Case Study in the Fenwei Plain - Zexuan Wang; Hongmei Xu; Rong Feng; Yunxuan Gu; Jian Sun; Suixin Liu; Ningning Zhang; Dan Li; Tao Wang; Linli Qu; Steven Sai Hang Ho; Zhenxing Shen; et al. (Advances in Atmospheric Sciences, 2023)

Spatiotemporal characteristics of high winds in Jilin Province during 1982–2021 - Xiao Wei; Kaiwei Li; Yunmeng Zhao; Yueting Yang; Guangzhi Rong; Ying Guo; Jiquan Zhang (International Journal of Climatology, 2023)
High winds are a type of catastrophic weather characterized by wind speeds over 10.8 m·s −1 , occurring in all seasons, and have become more frequent, impacting crop growth, agricultural production and quality of life. It is crucial to understand the spatial and temporal distribution patterns of high winds, as well as their speed and other characteristics, for logical planning of agricultural production and the creation of disaster resilience measures. This study applied the climate tendency, accumulative anomalies, theory of run, Mann–Kendall trend and Theil–Sen median to analyse the spatial and temporal distribution characteristics of the average wind speed and high wind days in Jilin Province, the probability of occurrence of high winds of various magnitudes in different eras, and the gale concentration degree (GCD) throughout Jilin Province for a total of 40 years from 1982 to 2021. The average wind speed and number of high wind days in Jilin Province have decreased over the past 40 years, and this trend has slowed over time. The average GCD in Jilin Province has shown an increasing trend over the last 40 years, with the average GCD being highest in Liouhe and lowest in Linjiang. In general, level six high winds were the main wind hazard level in Jilin Province, with the highest frequency occurring in different seasons and decades. In addition, the occurrence of high wind days is affected by global climate change and different underlying surfaces, which leads to maize and yield reduction. Research on the spatiotemporal distribution of high winds can provide important suggestions for the prevention and management of high wind disasters.

Dietary exposure risk assessment of pyrethroids in fruits and vegetables: a national scale investigation - Qianqian Li; Bei Li; Dawei Chen; Rong Zhang; Shuyan Liu; Shupeng Yang; Yi Li; Jianxun Li (Environmental Science and Pollution Research, 2023)

Characteristics of drought, low temperature, and concurrent events of maize in Songliao Plain - Yunmeng Zhao; Ying Guo; Rui Wang; Kaiwei Li; Guangzhi Rong; Jiquan Zhang; Chunli Zhao (International Journal of Climatology, 2023)
Maize is susceptible to drought and low temperatures. In recent years, drought, low temperatures, and their composite events have often occurred during the growth period of maize, causing a huge impact. In this study, maize in the Songliao Plain was used as the research object. Based on the crop water surplus deficit index (CWSDI) and heat index (F(T)), combined with the Theil–Sen median and Mann–Kendall tests (Sen–MK) and empirical orthogonal function (EOF), the temporal trends and spatial patterns of drought and low temperatures in different growth periods of maize were obtained. Copula modelling was used to analyse the joint probability distribution and return period of drought and low temperatures. The results showed that the temporal variation trend of the CWSDI was significantly different at different growth periods of maize, and there were different trends and spatial modal distributions. However, the temporal variation trend of F(T) was similar, showing a downward trend over the entire region. There was no obvious asymmetry or skew‐dependent structure in the distribution of concurrent events of drought and low temperature; however, the joint probability contours of different growth periods were biased to the upper left. The recurrence period of drought and low‐temperature concurrent events was within 2 years, and the recurrence period was basically between 2 and 5 years, with a reduction in drought or low temperatures.

Daphnia magna uptake and excretion of luminescence‐labelled polystyrene nanoparticle as visualized by high sensitivity real-time optical imaging - Yu-Hang Zhang; Rong-Yao Gao; Ze-Jun Wang; Qian-Qian Shao; Ya-Wen Hu; Hua-Bing Jia; Xiao-Jing Liu; Feng-Qin Dong; Li-Min Fu; Jian-Ping Zhang (Chemosphere, 2023)

Aquatic photolysis of high-risk chemicals of emerging concern from secondary effluent mediated by sunlight irradiation for ecological safety and the enhanced methods - Danyang Li; Xiaoyan Y. Ma; Shiying Zhang; Yongkun K. Wang; Yingnan Han; Rong Chen; Xiaochang C. Wang; Huu Hao Ngo (Water Research, 2023)

Multi-chambers of pilot-scale reactor enhanced partial nitritation performance - Kuo Zhang; Xinjue Li; Maofu Chen; Jingqi Sun; Kaiyu Rong; Sitong Liu (Science of The Total Environment, 2023)

Driving effects of land use and landscape pattern on different spontaneous plant life forms along urban river corridors in a fast-growing city - Xiaopeng Li; Yilun Li; Sining Zhang; Rong Lin; Mingkun Chen; Li Feng (Science of The Total Environment, 2023)

Quantum oscillations in field-induced correlated insulators of a moiré superlattice - Le Liu; Yanbang Chu; Guang Yang; Yalong Yuan; Fanfan Wu; Yiru Ji; Jinpeng Tian; Rong Yang; Kenji Watanabe; Takashi Taniguchi; Gen Long; Dongxia Shi; et al. (Science Bulletin, 2023)

Nudifloids A-N, structurally diverse 3,4-seco-labdane diterpenoids from Callicarpa nudiflora with inflammatory inhibitory activity - Xue-Rong Zhao; Xiao-Rong Sun; Xing-Jie Zhang; Xue-Wen Wu; Bin Cheng; Dong-Xuan Ni; Jia-Bi Huang; Rui-Han Zhang; Xiao-Li Li; Wei-Lie Xiao (Phytochemistry, 2023)

Chemical weathering in the Himalayan system in response to the evolution of the Indian summer monsoon since 37 ka - Long Tan; Jianguo Liu; Yun Huang; Rong Xiang; Shengfa Liu; Hui Zhang; Jingrui Li; Linghui Yu; Xuefa Shi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Toward a unified and refined Ordovician stratigraphy for the western Yangtze region, South China - Guang-Xu Wang; Yu-Nong Cui; Yan Liang; Rong-Chang Wu; Xin Wei; Fang-Yi Gong; Bing Huang; Xiao-Cong Luan; Peng Tang; Li-Xia Li; Xiao-Le Zhang; Yi-Chi Zhang; et al. (Palaeoworld, 2023)

Deciphering riverine dissolved organic matter biodegradation: Evidence from three-dimensional fluorescence - Rong Xu; Jing Zhang; Jianwei Li; Rui Liu; Maofei Ni; Guangneng Zeng (Journal of Environmental Chemical Engineering, 2023)

Catalytic cracking of supercritical n-dodecane over macro-meso-HZSM-5 coatings by vertical secondary growth - Di Rong; Jiaqi Zhang; Hao Li; Wen Guo; De Sun; Zhenheng Diao (Fuel, 2023)

Variations in the motility and biofilm formation abilities of Escherichia coli O157:H7 during noodle processing - Xiaohua He; Heer Ding; Zenghui Gao; Xiaofeng Zhang; Rong Wu; Ke Li (Food Research International, 2023)

BPA exposure enhances the metastatic aggression of ovarian cancer through the ERα/AKT/mTOR/HIF-1α signaling axis - Xin Xie; Yan Zhu; Huimin Cheng; Haili Li; Yadi Zhang; Rong Wang; Wenyong Li; Fengrui Wu (Food and Chemical Toxicology, 2023)

Mechanism of polycyclic aromatic hydrocarbons degradation in the rhizosphere of Phragmites australis: Organic acid co-metabolism, iron-driven, and microbial response - Ni-chen Zhang; Dan A; Yuan-qing Chao; Hai-Yan Li; Charles Li; Qing-qi Lin; Ya-ying Li; Rong-liang Qiu (Environmental Pollution, 2023)

Manganese oxide nanocrystals embedded porous Graphene-like network for electrosynthesis of H2O2 and construction of Self-powered aptasensor - Chuanpan Guo; Yiming Ruan; Shuai Zhang; Lun Kan; Heng Bian; Feilong Rong; Linghao He; Dongsheng Li; Miao Du; Zhihong Zhang (Chemical Engineering Journal, 2023)

The mechanisms of rapid seed germination in Caragana species adapted to low mean annual precipitation - Shi-Hua Qi; Guang-Qian Yao; Md. Mahadi Hasan; Hui Jiang; Xu-Dong Liu; Zheng-Fei Nie; Xia-Yi Zhang; Ya-Xian Du; Xue-Qian Tian; Feng-Ping Li; Xue-Rong Li; Xiang-Wen Fang (Trees, 2023)

Genome resequencing reveals genetic loci and genes conferring resistance to SMV-SC8 in soybean - Jiahao Chu; Wenlong Li; Zhanwu Yang; Zhenqi Shao; Hua Zhang; Shaoda Rong; Youbin Kong; Hui Du; Xihuan Li; Caiying Zhang (Theoretical and Applied Genetics, 2023)

Receiver function imaging of dense seismic array and deep dynamic mechanism beneath the eastern South China - Rubing Han; Dinghui Yang; Qiusheng Li; Rong Huang; Hongshuang Zhang; Jiangtao Li; Hao Chen; Zhuo Ye; Wei Fu (Science China Earth Sciences, 2023)

Molecular Hydrogen Mediates Neurorestorative Effects After Stroke in Diabetic Rats: the TLR4/NF-κB Inflammatory Pathway - Wan-Chao Yang; Ting-ting Li; Qiang Wan; Xin Zhang; Li-Ying Sun; Yu-Rong Zhang; Pei-Chen Lai; Wen-zhi Li (Journal of Neuroimmune Pharmacology, 2023)
Diabetes is an independent risk factor for stroke and amplifies inflammation. Diabetic stroke is associated with a higher risk of death and worse neural function. The identification of effective anti-inflammatory molecules with translational advantages is particularly important to promote perioperative neurorestorative effects. Applying molecular hydrogen, we measured blood glucose levels before and after middle cerebral artery occlusion (MCAO), 48-h cerebral oedema and infarct volumes, as well as 28-day weight, survival and neurological function. We also measured the levels of TLR4, NF-κB p65, phosphorylated NF-κB p65, catecholamines, acetylcholine and inflammatory factors. All measurements comprehensively showed the positive effect and translational advantage of molecular hydrogen on diabetic stroke. Molecular hydrogen improved the weight, survival and long-term neurological function of rats with diabetic stroke and alleviated changes in blood glucose levels before and after middle cerebral artery occlusion (MCAO), but no difference in circadian rhythm was observed. Molecular hydrogen inhibited the phosphorylation of NF-κB and significantly reduced inflammation. Molecular hydrogen mediates neurorestorative effects after stroke in diabetic rats. The effect is independent of circadian rhythms, indicating translational advantages. The molecular mechanism is related to the TLR4/NF-κB pathway and inflammation. Graphical abstract Molecular hydrogen (H 2 ) affects outcomes of ischemic stroke with diabetes mellitus (DM).

Effects of saline immersion on the physiological alterations of grass goldfish (Carassius auratus) during subsequent recovery in freshwater - Xiaowen Wang; Huijuan Li; Rong Zhang; Lili Liu; Hua Zhu (Fish Physiology and Biochemistry, 2023)

Efficacy of Aidi injection combined with chemotherapy, radiotherapy or chemoradiotherapy for unresectable esophageal cancer treatment: A meta-analysis and systematic review of 29 randomized controlled trials based on Asian populations (China) - Jinsheng Huang; Teng Fan; Yuming Rong; Xujia Li; Qi Jiang; Jun Kan; Huijuan Qiu; Qi Quan; Bei Zhang; Guifang Guo (European Journal of Clinical Pharmacology, 2023)

Lithium extraction from salt lake brines with high magnesium/lithium ratio: a review - Rong Zhu; Shixin Wang; C. Srinivasakannan; Shiwei Li; Shaohua Yin; Libo Zhang; Xiaobin Jiang; Guoli Zhou; Ning Zhang (Environmental Chemistry Letters, 2023)

Establishment of Agrobacterium-mediated transformation system to Juglans sigillata Dode ‘Qianhe-7’ - Rong Wei; Wen’e Zhang; Chunxiang Li; Zhenkun Hao; Dong Huang; Wenlong Zhang; Xuejun Pan (Transgenic Research, 2023)

Sediment sources and their impacts on a check dam-controlled watershed, Loess Plateau, China - Lu-lu Bai; Peng Shi; Wen Wang; Zhan-bin Li; Kun-xia Yu; Peng Li; Ling-zhou Cui; Rong-jian Shen; Mu-hong Guan; Xin-chun Du; Xun-le Zhang; Wen-fu Chen (Journal of Mountain Science, 2023)

Molecular detection and characterization of three novel parvoviruses belonging to two different subfamilies in zoo birds - Yan Wang; Yijie Sun; Xin Li; Rong Chen; Wang Li; Li Ji; Qifan Zhao; Likai Ji; Shixing Yang; Wen Zhang (Archives of Virology, 2023)

Secukinumab plays a synergistic role with starvation therapy in promoting autophagic cell death of hepatocellular carcinoma via inhibiting IL-17A-increased BCL2 level - Rong Tang; Linmei Zheng; Jinfang Zheng; Jincai Wu; Pingping Chen; Jiacheng Chen; Dafeng Xu; Yongchao Zeng; Qijin Li; Zhensheng Zhang (In Vitro Cellular & Developmental Biology - Animal, 2023)

Corrigendum to “Promotional effects of calcination temperature and H2O on the catalytic activity of Al-substituted MnAlO catalysts for low-temperature acetone oxidation” [Chemosphere 301 (2022) 134722] - Wan-Peng Zhang; Kun Wu; Junyi Zhao; Jun He; Leiping Wang; Hang Xiao; Jian-Bing Guo; Jian-Rong Li (Chemosphere, 2023)

Corrigendum to ’ Biochar enhances the biotransformation of organic micropollutants (OMPs) in an anaerobic membrane bioreactor treating sewage’ [Water Research 223 (2022) 118974] - Zhen Lei; Shixin Zhang; Lianxu Wang; Qian Li; Yu-You Li; Xiaochang C. Wang; Rong Chen (Water Research, 2023)

CircBCL11B acts as a ceRNA to facilitate 1,2-dichloroethane-induced astrocyte swelling via miR-29b-3p/AQP4 axis in SVG p12 cells - Yizhou Zhong; Bingli Zhang; Yuji Huang; Jiaxin Du; Boxuan Liang; Zhiming Li; Rongyi Ye; Bo Wang; Hongyi Xian; Xifei Yang; Weifeng Rong; Xiang Guo; et al. (Toxicology Letters, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

SlGH3.15, a member of the GH3 gene family, regulates lateral root development and gravitropism response by modulating auxin homeostasis in tomato - Guo Ai; Rong Huang; Dedi Zhang; Miao Li; Guobin Li; Wangfang Li; John K. Ahiakpa; Yikui Wang; Zonglie Hong; Junhong Zhang (Plant Science, 2023)

Exposure to real-ambient particulate matter induced vascular hypertrophy through activation of PDGFRβ - Hongxu Bao; Benying Li; Qing You; Xinyu Dun; Zhen Zhang; Yanan Liang; Yahui Li; Qixiao Jiang; Rong Zhang; Rui Chen; Wen Chen; Yuxin Zheng; et al. (Journal of Hazardous Materials, 2023)

Overexpression of Sedum SpHMA2, SpHMA3 and SpNramp6 in Brassica napus increases multiple heavy metals accumulation for phytoextraction - Zi Yang; Hai-Tao Wu; Hao Yang; Wan-Di Chen; Jia-Lan Liu; Fan Yang; Li Tai; Bin-Bin Li; Bo Yuan; Wen-Ting Liu; Yan-Feng Zhang; Yan-Rong Luo; et al. (Journal of Hazardous Materials, 2023)

Biochar enhanced organic matter transformation during pig manure composting: Roles of the cellulase activity and fungal community - Yanan Yin; Mengtong Li; Xiaohui Tao; Chao Yang; Wenrong Zhang; Haichao Li; Yucong Zheng; Xiaochang Wang; Rong Chen (Journal of Environmental Management, 2023)

Electromagnetic monitoring with local mesh for time-lapse monitoring of hydraulic fracturing - Zihao Zhang; Jianxin Liu; Rongwen Guo; Kouao Laurent Kouadio; Shaoquan Zhan; Aiyong Li; Rong Liu (Journal of Applied Geophysics, 2023)

Mesoporous zeolite Beta supported Ni nanoparticles for the catalytic hydroconversion of extraction portion from Jinjitan subbituminous coal to cycloalkanes - Juan Gao; Xian-Yong Wei; Yu-Hong Kang; Xiao-Qi Zhang; Ai-Min Wang; Xia-Long Li; Yong Gao; Guang-Hui Liu; Tao Chen; Yan-Jun Li; Xiang-Rong Ma; Jin-Jun Bai; et al. (Fuel, 2023)

Bioaccessibility and transport of lentil hull polyphenols in vitro, and their bioavailability and metabolism in rats - Fanghua Guo; Li Peng; Hua Xiong; Rong Tsao; Hua Zhang; Li Jiang; Yong Sun (Food Research International, 2023)

An oligosaccharide marker for rapid authentication of edible bird’s nest - Li-Feng Li; Hui-Yuan Cheng; Jun Lang; Tin-Long Wong; Ji-Xia Zhang; Wen-Jie Wu; Quan-Wei Zhang; Hau-Yee Kong; Check-Hei Lai; Hau-Yee Fung; Man Liu; Wan-Rong Bao; et al. (Food Chemistry, 2023)

Degradation of polymeric polyproanthocyanidins from black chokeberry by microwave-assisted nucleophilic technique of sulfite/catechin: Reaction kinetics, antioxidation and structural analysis - Miao Li; Pu Li; Yufeng Xu; Baiqing Zhang; Jinfeng Li; Weitian Zhong; Hui Zang; Hui Zheng; Haifeng Rong; Fengming Ma (Food Chemistry, 2023)

Co-folding of soy protein isolates and shellac by structural interplays to induce hydrogels - Yang Guo; Zhi-guo Zhang; Jing Cai; Wei-rong Li; Ling-yun Chen; Wei-cheng Wu (Food Hydrocolloids, 2023)

Molecular characterization and antimicrobial activity of NK-lysin in black scraper (Thamnaconus modestus) - Mei-Yi Liu; Yi-Rong Zhang; Jian-Hua Zhang; Liang Miao; Yun-Fei Dang; Chen-Jie Fei; Chang-Hong Li; Jiong Chen (Fish & Shellfish Immunology, 2023)

Cadmium exposure during puberty damages testicular development and spermatogenesis via ferroptosis caused by intracellular iron overload and oxidative stress in mice - Yi Wang; Jie Wu; Mingming Zhang; Huijuan OuYang; Mengyuan Li; Didi Jia; Rong Wang; Weiyi Zhou; Hao Liu; Yuan Hu; Yuyou Yao; Yehao Liu; et al. (Environmental Pollution, 2023)

Microplastics affect arsenic bioavailability by altering gut microbiota and metabolites in a mouse model - Shan Chen; Jin-Lei Yang; Yao-Sheng Zhang; Hong-Yu Wang; Xin-Ying Lin; Rong-Yue Xue; Meng-Ya Li; Shi-Wei Li; Albert L. Juhasz; Lena Q. Ma; Dong-Mei Zhou; Hong-Bo Li (Environmental Pollution, 2023)

Nitrogen addition mediates monospecific and mixed litter decomposition in a boreal peatland - Xiong-Fei Zhang; Nan-Hai Zhong; Rui Li; Fu-Xi Shi; Rong Mao (CATENA, 2023)

Extracellular Vesicles from NMN Preconditioned Mesenchymal Stem Cells Ameliorated Myocardial Infarction via miR-210-3p Promoted Angiogenesis - Yanan Pu; Chunyu Li; Xin Qi; Rui Xu; Liyang Dong; Yi Jiang; Qingyun Gong; Di Wang; Rong Cheng; Cheng Zhang; Yan Chen (Stem Cell Reviews and Reports, 2023)
Mesenchymal stem cell-derived extracellular vesicles (MSCs-EVs) possess cardioprotection in acute myocardial infarction. Nevertheless, the therapeutic intervention potential and the molecular mechanism of EVs from NMN (Nicotinamide mononucleotide) preconditioned hUCMSCs (N-EVs) in acute myocardial infarction remains unknown. In the present study, EVs from hUCMSCs (M-EVs) and N-EVs were identified by electron microscopy, immunoblotting and nanoparticle tracking analysis. Compared with M-EVs, N-EVs significantly increased the proliferation, migration, and angiogenesis of HUVECs. Meanwhile, N-EVs markedly reduced apoptosis and cardiac fibrosis and promoted angiogenesis in the peri-infarct region in the MI rats. A high-throughput miRNA sequencing and qPCR methods analysis revealed that miR-210-3p was abundant in N-EVs and the expression of miR-210-3p was obviously upregulated in HUVECs after N-EVs treated. Overexpression of miR-210-3p in HUVECs significantly enhanced the tube formation, migration and proliferative capacities of HUVECs. However, downregulation of miR-210-3p in HUVECs markedly decreased the tube formation, migration and proliferative capacities of HUVECs. Furthermore, bioinformatics analysis and luciferase assays revealed that EphrinA3 (EFNA3) was a direct target of miR-210-3p. Knockdown of miR-210-3p in N-EVs significantly impaired its ability to protect the heart after myocardial infarction. Altogether, these results indicated that N-EVs promoted the infarct healing through improvement of angiogenesis by miR-210-3p via targeting the EFNA3. Graphical Abstract Created with Biorender.com.

Considering flood scaling property in multi-objective calibration of the SWAT model: a case study in Zijinguan watershed, Northern China - Yanchen Zheng; Jianzhu Li; Ting Zhang; Youtong Rong; Ping Feng (Natural Hazards, 2023)

A systematic analysis and evaluation of nutritional composition of 23 strains of marine microalgae commonly used in aquaculture - Jia-Xing Zhang; Zhao-Shou Ran; Hai-Xuan Xie; Fei Kong; Meng-Qi Zhang; Yao Zhou; Yan-Rong Li; Kai Liao; Xiao-Jun Yan; Ji-Lin Xu (Algal Research, 2023)

Bioaccumulation determines the toxicity of carbon dots to two marine dinoflagellates - Yue-Yue Liu; Jia-Meng Li; Rong Ji; Hongguo Zhang; Wei Zhang; Ai-Jun Miao (Chemosphere, 2023)

DNA damage and up-regulation of PARP-1 induced by columbin in vitro and in vivo - Yufen Liao; Xin Wang; Guangyun Ran; Shiyu Zhang; Chutian Wu; Rong Tan; Ying Liu; Yan He; Ting Liu; Zhongxiu Wu; Ying Peng; Weiwei Li; et al. (Toxicology Letters, 2023)

Real-ambient particulate matter exposure-induced FGFR1 methylation contributes to cardiac dysfunction via lipid metabolism disruption - Benying Li; Yanan Liang; Hongxu Bao; Daochuan Li; Ying Zhang; Xinyu Dun; Zijian Xu; Andong Ji; Zhen Zhang; Yahui Li; Rong Zhang; Wen Chen; et al. (Science of The Total Environment, 2023)

Composite carrier enhanced bacterial adhesion and nitrogen removal in partial nitrification/anammox process - Xinjue Li; Yiming Feng; Kuo Zhang; Jianhang Zhou; Jingqi Sun; Kaiyu Rong; Sitong Liu (Science of The Total Environment, 2023)

Transcriptome sequencing and metabolite analysis reveal the single and combined effects of microplastics and di-(2-ethylhexyl) phthalate on Peneaus vannamei - Qiang-Qiang Shi; Xiao-Qian Zhang; Ze-Ming Zhang; Ning-Bo Wang; Hua Liu; Rong-Rong Zhang; Ai-Li Sun; Jiong Chen; Xi-Zhi Shi (Science of The Total Environment, 2023)

Intensification of the East Asian winter monsoon resulted in greater preservation of terrestrial organic carbon on the inner shelf of the East China Sea since the last 1400 years - Shuai Liu; Da-Wei Li; Rong Xiang; Meng Yu; Hailong Zhang; Li Li; Meixun Zhao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Complete genome sequence of one novel marine Pseudomonas sp. BSw22131 growing with dimethylsulfoniopropionate (DMSP) as the sole carbon source - Ting Hu; Yin-Xin Zeng; Yi-He Zhang; Yu Du; Wei Han; Hui-Rong Li; Wei Luo (Marine Genomics, 2023)

Does carbon emission trading mitigate firm's default risk? Evidence from China - Qingjun Zhang; Sulan Zhang; Rong Chen; Jing Li (Journal of Cleaner Production, 2023)

Generation of low-cadmium rice germplasms via knockout of OsLCD using CRISPR/Cas9 - Huamei Chen; Rong Ye; Ying Liang; Shuchang Zhang; Xiulian Liu; Chongjun Sun; Fangbai Li; Jicai Yi (Journal of Environmental Sciences, 2023)

Disinfection byproducts in indoor swimming pool water: Detection and human lifetime health risk assessment - Di Zhang; Shengkun Dong; Li Chen; Rong Xiao; Wenhai Chu (Journal of Environmental Sciences, 2023)

Formation of RNA adducts resulting from metabolic activation of spice ingredient safrole mediated by P450 enzymes and sulfotransferases - Xin Wang; Guangyun Ran; Yufen Liao; Bowen Gong; Chutian Wu; Rong Tan; Ying Liu; Shiyu Zhang; Ying Peng; Weiwei Li; Jiang Zheng (Food and Chemical Toxicology, 2023)

Bamboo-derived hydrophobic porous graphitized carbon for adsorption of volatile organic compounds - Yang Rong; Cong Pan; Kexin Song; Jong Chol Nam; Feng Wu; Zhixiong You; Zhengping Hao; Jinjun Li; Zhongshen Zhang (Chemical Engineering Journal, 2023)

Efficient removal of trace uranium from nuclear effluents using irradiation-functionalized fibrous adsorbents with very high salt tolerance - Yulong He; Liuhua Mu; Minglei Wang; Lijun Hu; Wanning Ren; Xuanzhi Mao; Xinxin Feng; Mingxing Zhang; Rong Li; Zhe Xing; Jiangtao Hu; Guozhong Wu (Chemical Engineering Journal, 2023)

Polyphenolic-modified cellulose acetate membrane for bone regeneration through immunomodulation - Qing-Yi Zhang; Jie Tan; Kai Huang; Rong Nie; Zi-Yuan Feng; Chen-Yu Zou; Qian-Jin Li; Jun Chen; Ning Sheng; Bo-Quan Qin; Zhi-Peng Gu; Li-Min Liu; et al. (Carbohydrate Polymers, 2023)

Chemical constituents from the root bark of Morus alba and their chemotaxonomic significance - Xiao-Cong Liu; Xuan-Qin Chen; Rong-Tao Li; Zhi-Jun Zhang (Biochemical Systematics and Ecology, 2023)

Interaction Between the Glymphatic System and α-Synuclein in Parkinson’s Disease - Yu Zhang; Cui Zhang; Xu-Zhong He; Zhen-Hua Li; Jing-Cai Meng; Rui-Ting Mao; Xin Li; Rong Xue; Qian Gui; Guo-Xing Zhang; Lin-Hui Wang (Molecular Neurobiology, 2023)

Identification and genetic characterisation of cathepsin L in Demodex - Hu Li; Guan Chenglin; Zhao Yae; Zhang Wanyu; Chai Rong (Experimental and Applied Acarology, 2023)

Assessing the Coordinate Development Between Economy and Ecological Environment in China’s 30 Provinces from 2013 to 2019 - Bing Rong; Cheng-jun Chu; Zhen Zhang; Ya-ting Li; Shu-hao Yang; Qian Wang (Environmental Modeling & Assessment, 2023)

Kuroshio Intrusion Combined with Coastal Currents Affects Phytoplankton in the Northern South China Sea Revealed by Lipid Biomarkers - Yaoyao Wang; Rong Bi; Jiawei Gao; Hailong Zhang; Li Li; Yang Ding; Gui’e Jin; Meixun Zhao (Journal of Ocean University of China, 2023)

Genome-wide DNA methylation and transcription analysis reveal the potential epigenetic mechanism of heat stress response in the sea cucumber Apostichopus japonicus - Mengyang Chang; Jianlong Ge; Meijie Liao; Xiaojun Rong; Yingeng Wang; Bin Li; Xinrong Li; Jinjin Wang; Zheng Zhang; Yongxiang Yu; Chunyuan Wang (Frontiers in Marine Science, 2023)
DNA methylation is an important epigenetic modification that regulates many biological processes. The sea cucumber Apostichopus japonicus often suffers from heat stress that affects its growth and leads to significant economic losses. In this study, the mRNA expression patterns and DNA methylation characteristics in the body wall of A. japonicus under heat stress were analyzed by whole-genome bisulfite sequencing (WGBS) and transcriptome sequencing (RNA-seq). We found that CpG was the main DNA methylation type, and heat stress caused a significant increase in the overall methylation level and methylation rate, especially in the intergenic region of the A. japonicus genome. In total, 1,409 differentially expressed genes (DEGs) and 17,927 differentially methylated genes (DMGs) were obtained by RNA-seq and WGBS, respectively. Association analysis between DNA methylation and transcription identified 569 negatively correlated genes in both DMGs and DEGs, which indicated that DNA methylation affects on transcriptional regulation in response to heat stress. These negatively correlated genes were significantly enriched in pathways related to energy metabolism and immunoregulation, such as the thyroid hormone signaling pathway, renin secretion, notch signaling pathway and microRNAs in cancer. In addition, potential key genes, including heat shock protein ( hsp70 ), calcium-activated chloride channel regulator 1( clca1 ), and tenascin R ( tnr ), were obtained and their expression and methylation were preliminarily verified. The results provide a new perspective for epigenetic and transcriptomic studies of A. japonicus response to heat stress, and provide a reference for breeding sea cucumbers resistant to high temperatures.

Evaluation of negative effect of Naphthenic acids (NAs) on physiological metabolism and polycyclic aromatic hydrocarbons adsorption of Phragmites australis - Hui Jia; Guang-xi Zhang; Yi-fan Wu; Wei-wei Dai; Quan-bin Xu; Shu Gan; Xiu-yun Ju; Zhao-zhong Feng; Rong-peng Li; Bo Yuan (Chemosphere, 2023)

The effectiveness of eight-years phosphorus reducing inputs on double cropping paddy: Insights into productivity and soil-plant phosphorus trade-off - Ning Su; Guixian Xie; Zhiwei Mao; Qiaorong Li; Tian Chang; Yuping Zhang; Jianwei Peng; Xiangmin Rong; Gongwen Luo (Science of The Total Environment, 2023)

Efficient inactivation of the contamination with pathogenic microorganisms by a combination of water spray and plasma-activated air - Li Guo; Pengyu Zhao; Yikang Jia; Tianhui Li; Lingling Huang; Zifeng Wang; Dingxin Liu; Zhanwu Hou; Yizhen Zhao; Lei Zhang; Hua Li; Yu Kong; et al. (Journal of Hazardous Materials, 2023)

Changes in cropland soil carbon through improved management practices in China: A meta-analysis - Bai-Jian Lin; Ruo-Chen Li; Mu-Yu Yang; Zheng-Rong Kan; Ahmad Latif Virk; Yves N′Dri Bohoussou; Xin Zhao; Yash Pal Dang; Hai-Lin Zhang (Journal of Environmental Management, 2023)

Impact of electron donors on chlorinated ethane degradation and native bacteria response in aged contaminated groundwater: A systematic study with insights - Jiuhao Song; Yi Li; Naijin Wu; Peizhong Li; Ji Zhang; Liming Rong; Yun Song (International Biodeterioration & Biodegradation, 2023)

Synergistic and antagonistic effects of preharvest salicylic acid and postharvest 1-methylcyclopropene treatments on the storage quality of apricot - Changchang Liang; Xinzhi Cui; Chanchan Sun; Sunxiang Ye; Ningxin Huang; Rong Chen; Aidi Zhang; Yanqing Yang; Hansheng Gong; Shuyang Sun; Fengjun Guo; Xinguang Fan; et al. (Food Chemistry, 2023)

Shaking table tests and seismic assessment of a full-scale precast concrete sandwich wall panel structure with bolt connections - Jia-Xuan He; Zhao-Dong Xu; Lian-Yu Zhang; Zhi-Hua Lin; Zhong-Wei Hu; Qiang-Qiang Li; Yao-Rong Dong (Engineering Structures, 2023)

Dual-functional electrostatic self-assembly nanoparticles enable suppressed defects and improved charge transport in perovskite optoelectronic devices - Hu Zhang; Pengfei Xu; Zhiliang Chen; Hengkai Zhang; Wenlong Shao; Yanhui Li; Jianfeng Yao; Da Rong; Duanwangde Liu; Liangpan Yang; Siliang Wang; Pengbin Gui; et al. (Chemical Engineering Journal, 2023)

Exploring the potential anti-Alzheimer disease mechanisms of Alpiniae Oxyphyliae Fructus by network pharmacology study and molecular docking - Rong-Rong Zhen; Yan-Jie Qu; Li-Min Zhang; Chao Gu; Min-Rui Ding; Lei Chen; Xiao Peng; Bing Hu; Hong-Mei An (Metabolic Brain Disease, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

Experimental study of high-strength steel fiber concrete exterior beam-column joints with high-strength steel reinforcements - Jianxin Zhang; Xiaoxue Zhao; Xian Rong; Yanyan Li (Bulletin of Earthquake Engineering, 2023)

Effects of long-term grazing exclusion on vegetation structure, soil water holding capacity, carbon and nitrogen sequestration capacity in an alpine meadow on the Tibetan Plateau - Yong-sheng Yang; Fa-wei Zhang; Xian-rong Xie; Jun-bang Wang; Ying-nian Li; Xiao-tao Huang; Hui-ting Li; Hua-kun Zhou (Journal of Mountain Science, 2023)

Risk assessment and environmental determinants of urinary phthalate metabolites in pregnant women in Southwest China - Nian Wu; Lin Tao; Kunming Tian; Xia Wang; Caidie He; Songlin An; Yingkuan Tian; Xiang Liu; Wei Chen; Haonan Zhang; Pei Xu; Dengqing Liao; et al. (Environmental Science and Pollution Research, 2023)

Radon exhalation from cement-based materials under accelerated carbonation - Rong Yang; Jie Wang; Xiaowen Zhang; Jie Li; Mianbiao Chen (Environmental Science and Pollution Research, 2023)

Mechanism of YY1 mediating autophagy dependent ferroptosis in PM2.5 induced cardiac fibrosis - Huaifang Hu; Lipeng Li; Huaxing Zhang; Yaling Zhang; Qingping Liu; Meiyu Chen; Jie Ning; Yaxian Pang; Wentao Hu; Yujie Niu; Rong Zhang (Chemosphere, 2023)

Density estimation method of mature wheat based on point cloud segmentation and clustering - Rong Zou; Yu Zhang; Jin Chen; Jinyan Li; Wenjie Dai; Senlin Mu (Computers and Electronics in Agriculture, 2023)

Molecular docking and molecular dynamics simulation study on the toxicity mechanism of bongkrekic acid - Hongmei Li; Zhen Liang; Ying Li; Jiazhen Wen; Rong Zhang (Toxicon, 2023)

Ex vivo coronary endothelial cell activation associated with indoor coal combustion initiated atherosclerosis - Wanjun Zhang; Yaxian Pang; Wenting Cheng; Tao Wang; Yanting Li; Xin Li; Jianzhong Zhang; Xiaowen Xia; Yuxin Zheng; Rong Zhang; Jinglong Tang (Science of The Total Environment, 2023)

Novel one-point calibration strategy for high-throughput quantitation of microcystins in freshwater using LC-MS/MS - Huiyan Zhang; Yanshen Li; Mohamed F. Abdallah; Haiguang Tan; Jianxun Li; Shuyan Liu; Rong Zhang; Feifei Sun; Yi Li; Shupeng Yang (Science of The Total Environment, 2023)

Overexpression of two CONSTANS-like 2 (MiCOL2) genes from mango delays flowering and enhances tolerance to abiotic stress in transgenic Arabidopsis - Rong-Zhen Liang; Cong Luo; Yuan Liu; Wan-Li Hu; Yi-Hang Guo; Hai-Xia Yu; Ting-Ting Lu; Shu-Quan Chen; Xiu-Juan Zhang; Xin-Hua He (Plant Science, 2023)

Eudesmane−type sesquiterpenes from the rhizomes of Atractylodes macrocephala and their bioactivities - Hai-Xin Zhang; Jin-Guang Si; Jing-Rong Li; Meng Yu; Ling-Ling Qin; Chen-Xu Zhao; Tao Zhang; Zhong-Mei Zou (Phytochemistry, 2023)

Four new glycosides from Gerbera piloselloides - Ha Gao; Chen-Xu Zhao; Xin-Yao Luo; Jing-Rong Li; Xiao-Chuan Ye; Tao Zhang; Zhong-Mei Zou (Phytochemistry Letters, 2023)

Negatively charged nano-hydroxyapatite can be used as a phosphorus fertilizer to increase the efficacy of wollastonite for soil cadmium immobilization - Rong Huang; Peng Mao; Lei Xiong; Guoming Qin; Jinge Zhou; Jingfan Zhang; Zhian Li; Jingtao Wu (Journal of Hazardous Materials, 2023)

Effective roxarsone (ROX) and arsenate (As(V)) sequestration from water with magnetic hollow Fe3O4-based Mg/Al layered double hydroxide: Performance and mechanism - Zhipan Wen; Shen Li; Ge Zhang; Runqiao Chen; Yalei Zhang; Xiaoping Liao; Gang Cheng; Rong Chen (Journal of Cleaner Production, 2023)

Fertility assessment and nutrient conversion of hydrochars derived from co-hydrothermal carbonization between livestock manure and corn cob - Chao-sheng Li; Rong-rong Cai; Abdulla Hasan; Xiao-luan Lu; Xiao-xiao Yang; Yan-guo Zhang (Journal of Environmental Chemical Engineering, 2023)

Refractory organics removal in PMS and H2O2/PMS oxidation system activated by biochar/nZVI/MoS2 composite: Synthesis, performance, mechanism and dosing methods - Hao Sun; Baoyong Zhang; Na Wang; Nianbo Zhang; Yunqian Ma; Lihua Zang; Zhen Li; Rong Xue (Journal of Environmental Chemical Engineering, 2023)

The emergence of novel macrolide resistance island in Macrococcus caseolyticus and Staphylococcus aureus of food origin - Feng Zhang; Shi Wu; Jingsha Dai; Jiahui Huang; Jumei Zhang; Miao Zhao; Dongli Rong; Yuanyu Li; Juan Wang; Moutong Chen; Liang Xue; Yu Ding; et al. (International Journal of Food Microbiology, 2023)

Landscapes drive the dispersal of Monochamus alternatus, vector of the pinewood nematode, revealed by whole-genome resequencing - Xiaohong Han; Yechen Li; Wanlong Huang; Rong Wang; Xia Hu; Guanghong Liang; Shiguo Huang; Chunlan Lian; Feiping Zhang; Songqing Wu (Forest Ecology and Management, 2023)

A 2D mesoporous hydrazone covalent organic framework for selective detection and ultrafast recovery of Au(III) from electronic waste - Li Zhang; Jia-Qi Fan; Qiong-Qing Zheng; Sai-Jin Xiao; Cheng-Rong Zhang; Shun-Mo Yi; Xin Liu; Wei Jiang; Quan-Gen Tan; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Selective separation of volatile fatty acids, nitrogen and phosphorus from anaerobic acidogenic fermentation via forward osmosis membrane process - Xian-Zheng Zhu; Long-Fei Wang; Xin-Rong Pan; Feng Zhang; Min-Sheng Huang; Wen-Wei Li; Hou-Qi Liu (Chemical Engineering Journal, 2023)

Extraction and characterization of waxy and normal barley β-glucans and their effects on waxy and normal barley starch pasting and degradation properties and mash filtration rate - Qiao Li; Juan Liu; Huisheng Zhai; Zhihui Zhang; Rong Xie; Futong Xiao; Xingquan Zeng; Yuhong Zhang; Zhongyi Li; Zhifen Pan (Carbohydrate Polymers, 2023)

Community succession of microbial populations related to C N P S biological transformations regulates product maturity during cow-manure-driven composting - Xin Liu; Xiangmin Rong; Junyan Yang; Han Li; Wang Hu; Yong Yang; Guoliang Jiang; Rusheng Xiao; Xingxiang Deng; Guixian Xie; Gongwen Luo; Jiachao Zhang (Bioresource Technology, 2023)

Carrier type affects anammox community assembly, species interactions and nitrogen conversion - Baoyong Zhang; Nianbo Zhang; Ao He; Chen Wang; Zhen Li; Guanjun Zhang; Rong Xue (Bioresource Technology, 2023)

Diagnosis of atmospheric circulation shifts in the central Tibetan Plateau: Evidence from stable isotopes - Yao Li; Wusheng Yu; Lide Tian; Stephen Lewis; Kei Yoshimura; Cheng Wang; Jiangpeng Cui; Yaoming Ma; Rong Guo; Jingyi Zhang; Zhaowei Jing; Lili Shao; et al. (Atmospheric Research, 2023)

Environmental Factors Influence the Effects of Biochar on the Bioavailability of Cd and Pb in Soil Under Flooding Condition - Honghong Li; Zhou Li; Limei Huang; Xiaoming Mao; Yuxuan Dong; Shilong Fu; Rong Su; Yihan Chang; Chuan Zhang (Water, Air, & Soil Pollution, 2023)

Remodeled CD146+CD271+ Bone Marrow Mesenchymal Stem Cells from Patients with Polycythemia Vera Exhibit Altered Hematopoietic Supportive Activity - Chao Chen; Mingying Zhang; Rong Li; Jiajia Yuan; Jinqiang Yan; Yuhui Zhang; Wen Xing; Jie Bai; Yuan Zhou (Stem Cell Reviews and Reports, 2023)

Evaluation of deep learning algorithms for landslide susceptibility mapping in an alpine-gorge area: a case study in Jiuzhaigou County - Di Wang; Rong-hao Yang; Xiao Wang; Shao-da Li; Jun-xiang Tan; Shi-qi Zhang; Shuo-you Wei; Zhang-ye Wu; Chao Chen; Xiao-xia Yang (Journal of Mountain Science, 2023)

A near-infrared fluorescent probe for monitoring abnormal mitochondrial viscosity in cancer and fatty-liver mice model - Jing-Jing Chao; Hui Zhang; Zhi-Qing Wang; Qiao-Rong Liu; Guo-Jiang Mao; Dong-Hua Chen; Chun-Yan Li (Analytica Chimica Acta, 2023)

Enhanced phytoremediation of atrazine-contaminated soil by vetiver (Chrysopogon zizanioides L.) and associated bacteria - Faming Zhang; Shixian Sun; Yuhong Rong; Lili Mao; Shuchun Yang; Ling Qian; Rongbiao Li; Yi Zheng (Environmental Science and Pollution Research, 2023)

A new acylated iridoid and other chemical constituents from Valeriana jatamansi and their biological activities - Yun Wang; Dao-Qun Shi; Na Jiang; Kai-Rui Rao; Shi-Xian Zhang; Dan Liu; Rong-Tao Li; Hong-Mei Li (Natural Product Research, 2023)

A novel TiO2-x/TiN@ACB composite for synchronous photocatalytic Cr(VI) reduction and water photothermal evaporation under visible/infrared light illumination - Hossam Zakaria; Yi Li; Mohamed M. Fathy; Xinyi Zhou; Xinyan Xiong; Ye Wang; Shengxiang Rong; Chi Zhang (Chemosphere, 2023)

Nondestructive and rapid method for sex identification of the tropical sea cucumber Holothuria scabra by anal swab sampling - Zixuan E; Chuhang Cheng; Feifei Wu; Chunhua Ren; Rong Chen; Yingzhu Rao; Bo Ma; Xiao Jiang; Peng Luo; Xiaomin Li; Xin Zhang; Fajun Jiang; et al. (Aquaculture, 2023)

A new method for wear estimation of TBM disc cutter based on energy analysis - Lei She; She-rong Zhang; Chao Wang; Yan-long Li; Min Du (Tunnelling and Underground Space Technology, 2023)

Trace elements in red swamp crayfish (Procambarus clarkii) in China: Spatiotemporal variation and human health implications - Hui Li; Huaiyan Li; Haiting Zhang; Jing Cao; Tao Ge; Jiale Gao; Yan Fang; Wenling Ye; Ting Fang; Yanhong Shi; Rong Zhang; Xinju Dong; et al. (Science of The Total Environment, 2023)

Moderate physical activity against effects of short-term PM2.5 exposure on BP via myokines-induced inflammation - Mengqi Wu; Yaxian Pang; Meiyu Chen; Lipeng Li; Lina Yan; Jie Ning; Qingping Liu; Yaling Zhang; Tao Jiang; Aijuan Kang; Xiaoyan Huang; Wentao Hu; et al. (Science of The Total Environment, 2023)

Life cycle assessment-driven collaborative optimization model of power dry cutting for face-hobbing hypoid gear production - Han Ding; Shifeng Rong; Kaibin Rong; Jinyuan Tang; Zhenyu Zhou; Jiange Zhang; Guowen Li (Journal of Cleaner Production, 2023)

Quantitative monitoring and potential mechanism of the secondary corrosion risk of PAH-contaminated soil remediated by persulfate oxidation - Zhenxia Wang; Jiuhao Song; Wenyi Yuan; Yi Li; Naijin Wu; Xiang Li; Liming Rong; Haijian Wang; Ji Zhang; Wenxia Wei; Peizhong Li (Journal of Environmental Management, 2023)

Effects of different pretreatment methods on drying kinetics, three-dimensional deformation, quality characteristics and microstructure of dried apple slices - Jun-Wen Bai; Lu Zhang; Joshua H. Aheto; Jian-Rong Cai; Yu-Chi Wang; Li Sun; Xiao-Yu Tian (Innovative Food Science & Emerging Technologies, 2023)

Mo isotopes archive oceanic sediments in post-orogenic lithospheric mantle - Feng Huang; Jie Li; Jifeng Xu; Jianlin Chen; Baodi Wang; Pan Hu; Rong Xu; Yunchuan Zeng; Le Zhang; Ting Zhou (Geochimica et Cosmochimica Acta, 2023)

A study on molecular structural evolution of type II kerogen in a gold tube thermal system: Insights from solid-state 13C NMR - Deping Zhang; Huairen Cao; Yan Lei; Hao Wu; Xiaoyu Wang; Xuelian Guo; Jianping Yan; Shuhua Wang; Tianchi Shi; Haolin Li; Yan-rong Zou; Ping'an Peng (Fuel, 2023)

Oligosaccharide analysis of the backbone structure of the characteristic polysaccharide of Dendrobium officinale - Tin-Long Wong; Li-Feng Li; Ji-Xia Zhang; Quan-Wei Zhang; Xue-Ting Zhang; Li-Shuang Zhou; Hau-Yee Fung; Lei Feng; Hui-Yuan Cheng; Chu-Ying Huo; Man Liu; Wan-Rong Bao; et al. (Food Hydrocolloids, 2023)

Mice kidney biometabolic process analysis after cantharidin exposure using widely-targeted metabolomics combined with network pharmacology - Tianmu He; Lijuan Xiong; Yixin Zhang; Rong Yan; Ming Yu; Meichen Liu; Liu Liu; Cancan Duan; Xiaofei Li; Jianyong Zhang (Food and Chemical Toxicology, 2023)

The association of air pollutants with hospital outpatient visits for child and adolescence psychiatry in Shenzhen, China - Dong Fang; Wang Bing; Han Yao-hui; Jing Chun-xia; Zhang Ying; Liu Xing-li; Tian Hua-wei; Xiang Ying-jun; Liao Wan-wei; Li Xiu-juan; Fan Dong-yong; Yang Wei-ting; et al. (Environmental Research, 2023)

Combining a novel biofilm reactor with a constructed wetland for rural, decentralized wastewater treatment - Rui Zhang; Xianchang Liu; Lutian Wang; Pan Xu; Kai Li; Xiaoxiao Chen; Rong Meng; Yuewu Pu; Xuetong Yang; Diederik P.L. Rousseau; Stijn W.H. Van Hulle (Chemical Engineering Journal, 2023)

Petal-like hierarchical Co3O4/N-doped porous carbon derived from Co-MOF for enhanced peroxymonosulfate activation to remove tetracycline hydrochloride - Qingqing Li; Zhujuan Ren; Yutong Liu; Chibin Zhang; Jiadi Liu; Rong Zhou; Yuanqing Bu; Feifei Mao; Hua Wu (Chemical Engineering Journal, 2023)

Programmable phthalocyanine-iron-based nanoreactor for fluorescence/magnetic resonance dual-modality imaging-guided sono/chemodynamic therapies - Dong Li; Jie Pan; Shuyu Xu; Bingwei Cheng; Shuaiying Wu; Qixuan Dai; Mei-Rong Ke; Bi-Yuan Zheng; Chengchao Chu; Chao Liu; Yang Zhang; Xiao Xu; et al. (Chemical Engineering Journal, 2023)

Micro-mesoporous graphitized carbon fiber as hydrophobic adsorbent that removes volatile organic compounds from air - Min Yan; Yang Rong; Feng Wu; Zhixiong You; Dashan Wang; Xudong Yang; Zhengping Hao; Jinjun Li; Zhongshen Zhang (Chemical Engineering Journal, 2023)

Regulatory effects mediated by ulvan oligosaccharide and its zinc complex on lipid metabolism in high-fat diet-fed mice - Yongzhou Chi; Zhihua Wu; Chunying Du; Man Zhang; Xinyu Wang; Aowei Xie; Peng Wang; Rong Li (Carbohydrate Polymers, 2023)

The driving factors and buffering mechanism regulating cropland soil acidification across the Sichuan Basin of China - Aiwen Li; Chengji Li; Yuanyuan Zhang; Qian Deng; Hongyan Fang; Bin Zhao; Min Ran; Liangying Song; Jingling Xue; Qi Tao; Rong Huang; Yiding Li; et al. (CATENA, 2023)

The genomic, transcriptomic, and immunological profiles of perineural invasion in pancreatic ductal adenocarcinoma - Shu-Heng Jiang; Rong-Kun Li; De-Jun Liu; Jun-Li Xue; Min-Hao Yu; Shan Zhang; Li-Min Liu; Jun-Feng Zhang; Rong Hua; Yong-Wei Sun; Xu Wang; Qin Yang; et al. (Science China Life Sciences, 2023)

IL-18BP Alleviates Anxiety-Like Behavior Induced by Traumatic Stress via Inhibition of the IL-18R-NLRP3 Signaling Pathway in a Mouse Model of Hemorrhagic Shock and Resuscitation - Li-Min Zhang; Dong-Xue Zhang; Rong-Xin Song; Jin-Meng Lv; Lu-Ying Wang; Zhi-You Wu; Hui-Tao Miao; Yan-Bo Zhou; Wei Zhang; Yue Xin; Yan Li (Molecular Neurobiology, 2023)

Nitric Oxide Enhances Salt Tolerance in Tomato Seedlings by Regulating Endogenous S-nitrosylation Levels - Chunlei Wang; Lijuan Wei; Jing Zhang; Dongliang Hu; Rong Gao; Yayu Liu; Li Feng; Wenting Gong; Weibiao Liao (Journal of Plant Growth Regulation, 2023)

Exposure–response relationship between temperature, relative humidity, and varicella: a multicity study in South China - Yihan Li; Jialing Li; Zhihua Zhu; Weilin Zeng; Qi Zhu; Zuhua Rong; Jianxiong Hu; Xing Li; Guanhao He; Jianguo Zhao; Lihua Yin; Yi Quan; et al. (Environmental Science and Pollution Research, 2023)

Spatiotemporal impacts of climate change and human activities on water resources and ecological sensitivity in the Mekong subregion in Cambodia - Yi Lin; Yu Rong; Lang Li; Fengting Li; Hanchao Zhang; Jie Yu (Environmental Science and Pollution Research, 2023)